Synthesis, DFT, electrochemical, biological and DNA-interaction studies of a novel copper(II) complex of salicylic acid and N-tosyl substituted benzimidazole - Rashid N.; Kiran A.; Ahmad I.; Ashraf Z.; Mohd. Yamin B.; Rafiq M. (Taylor and Francis Ltd., 2024)
Indexed by Scopus